The Dynamics of Friendship Environment on the Personality of Sociology Education Students (Faculty of Teacher Training and Education), Universitas Sultan Ageng Tirtayasa - Vhia, Vhia Aulia Salsabilla; Qurrotun’ainKeysha Nabih; Ahmad, Ahmad; Fauzi, Agung (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study aims to analyze the dynamics of friendship environments and their influence on the personality formation of Sociology Education students at the Faculty of Teacher Training and Education, Universitas Sultan Ageng Tirtayasa. This research employed a qualitative descriptive approach involving five students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model. The findings show that friendship dynamics are influenced by shared interests, backgrounds, interaction intensity, social media, academic goals, and conflict experiences. Friendship environments contribute to personality formation through social interaction, social support, and shared experiences. Positive impacts include increased self-confidence, adaptability, learning motivation, and communication skills, while negative impacts include interpersonal conflicts and emotional pressure. These findings indicate that friendship environments play a consistent role in shaping students’ personalities during their university life. The study concludes that friendship environments are important factors in students’ personality development.